2011
DOI: 10.3109/17483107.2011.635405
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis rejection in acquired major upper-limb amputees: a population-based survey

Abstract: Clinicians should be aware of the increased risk of rejection in proximal ULAs, elderly ULAs and in women. Emphasising individual needs will probably facilitate successful prosthetic fitting. Improved prosthesis quality and individualised prosthetic training may increase long-term prosthesis use. Further studies of the effect of prosthetic training and of the reasons for rejection of different prosthetic types are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
127
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(150 citation statements)
references
References 36 publications
3
127
0
1
Order By: Relevance
“…Supportive of this view, a review of the English language literature over a 25-year period observed that, while technology had improved, prosthetic limb rejection rates have not been decreasing, with 35 % of paediatric and 23 % of adult amputee populations discontinuing use of their prosthetic limb [49]. In a separate study, 13.4 % of Norwegian major upper limb amputees discontinued use of their prosthesis mainly due to poor prosthetic comfort, function and control [50].…”
Section: Pattern Recognition Controlmentioning
confidence: 99%
“…Supportive of this view, a review of the English language literature over a 25-year period observed that, while technology had improved, prosthetic limb rejection rates have not been decreasing, with 35 % of paediatric and 23 % of adult amputee populations discontinuing use of their prosthetic limb [49]. In a separate study, 13.4 % of Norwegian major upper limb amputees discontinued use of their prosthesis mainly due to poor prosthetic comfort, function and control [50].…”
Section: Pattern Recognition Controlmentioning
confidence: 99%
“…However, the actual impact of these technologies on patients' lives has been documented in only two case reports [10][11]. The question remains whether advanced devices may be more suited for some people with amputation and less for others based on underlying patient characteristics [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…HE human hand and arm are essential for a person to perform many daily life activities, including communication and interaction [1]. The loss of hand and wrist function after upper-limb amputation leads to significant disability [2].…”
Section: Introductionmentioning
confidence: 99%